Long noncoding RNA maternally expressed gene 3 improves trophoblast dysfunction and inflammation in preeclampsia through the Wnt/β-Catenin/nod-like receptor pyrin domain-containing 3 axis - Liang, Yue; Wang, Ping; Shi, Yueyang; Cui, Bihong; Meng, Jinlai (Frontiers in Molecular Biosciences, 2022)
Inadequate trophoblastic infiltration and resulting placental hypoxia and inflammation comprise the core pathological basis of preeclampsia (PE). Maternally expressed gene 3 (MEG3) is known to be involved in the pathogenesis of preeclampsia by inhibiting the migration and invasion of trophoblasts and promoting their apoptosis. Nevertheless, the specific underlying downstream molecular mechanism of MEG3 is less well characterized. In this study, we detected lower expression levels of MEG3 and β‐catenin and higher expression of Nod-like receptor pyrin domain-containing 3 (NLRP3) in placental tissues of pregnant women with sPE than in normal pregnancies. Elevated serum levels of IL-1β and TNF-α were also observed in the sPE group. Then, we established a hypoxia/reoxygenation (H/R) model to mimic preeclampsia. Similar results with sPE group were found in the H/R group compared with the control group. In addition, suppressive trophoblast proliferation, migration and invasion and increases in the apoptotic rate and inflammation were also detected in the H/R group. Notably, overexpressing MEG3 markedly improved trophoblast dysfunction and inflammation caused by H/R. However, the effects of MEG3 on trophoblasts, whether upregulated or downregulated, can be reversed by DKK-1 (Wnt/β‐catenin inhibitor) and MCC950 (NLRP3 inhibitor). The current study revealed that MEG3 regulates trophoblast function and inflammation through the Wnt/β-catenin/NLRP3 axis and provided new insights into the pathogenesis of preeclampsia.